The ecology and management of the fishes of the Okavango Delta, Botswana, with particular reference to the role of the seasonal floods - Merron, Glen Steven (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1991)
The Okavango is a vast inland delta system in northern Botswana which receives an annual flood from the highlands of southern Angola. There are distinct communities of fish in the Okavango which can be separated from each other by the physical characteristics of the different habitat types with which they co-evolved. This thesis provides an account of the biology and ecology of selected fish species in the Okavango Delta. Their response to the annual flood regime, and the environmental factors which limit their distribution and abundance, are examined. The thesis emphasizes the importance of water fluctuations in determining the nature of the fish fauna and the reaction of the fishes in terms of community structure, movements, breeding, predator-prey interactions and feeding. Four major ecotones were studied in the Okavango Delta. In the riverine floodplain and perennial swamp ecotones a higher species diversity was recorded than in the seasonal swamp and drainage rivers ecotones where diversity was lowest and comprised mainly of smaller fish species. A greater variety of habitat types was associated with the riverine floodplain and perennial swamp relative to the seasonal swamp and drainage rivers. The variety of habitat types between ecotones is associated with the degree of flood inundation in the respective ecotones. During the course of this study, annual recruitment of fish into the drainage rivers was from refugia in the seasonal swamp whereas the greatest degree of lateral and longitudinal movement was in the riverine floodplain and perennial swamp. Movement was in response to both biological requirements, such as availability of food and spawning sites, and physical features of the environment, such as the changing water depth. The total catch per unit effort (CPUE) of fish throughout the year was more constant in the riverine floodplain and perennial swamp than in the seasonal swamp and drainage rivers where CPUE fluctutated widely. An increase in CPUE during the duration of this study was apparent and related to the magnitude of the annual flood. In contrast to most other African wetlands, the arrival of the annual flood in the Okavango Delta coincides largely with the dry winter months. This situation presented an opportunity to compare the influence of floods and water temperature on the reproductive biology of the selected fish species. The results show a definite pattern and indicate that both the flood cycle and increased water temperatures greatly influence the breeding cycles of the selected species. The tilapia Oreochromis andersonii exhibited a considerable degree of phenotypic plasticity. Fish from the seasonally inundated areas showed a smaller mean size, egg size and larger number of eggs relative to fish in the perennially flooded areas. The size at sexual maturity was also smaller. These different reproductive characteristics exhibited by O. andersonii are dependent on the degree of water retention in the different habitats. The fishes of the Okavango have adopted other reproductive strategies to survive the changing environmental conditions brought about by an annual flood cycle. These strategies include the construction of foam nests, as described for Hepsetus odoe, for guarding the young and to provide an oxygen-rich environment. Two main non-piscivorous feeding pathways were identified in the Okavango. These are a detritus pathway based on dead plant and animal material, and an epiphyte pathway, based on algae and invertebrates that are attached to plant stems. Seasonal changes in diet in relation to the annual flood were recorded. The most dramrtic change was demonstrated by the catfish Clarias gariepinus which congregates in mass aggregations in the northern regions of the Delta and hunt in packs. Pack-hunting by catfish is a regular response to the annual fluctuations in water level. It is my conclusion that the main flow of biotic and abiotic stimuli within the Okavango Delta originates from the relatively hydrologically stable riverine floodplain and perennial swamp ecotones to the widely fluctuating seasonal swamp and drainage rivers ecotones. The relatively stable ecotones allow a diverse and biotically interdependent fish community to develop, whereas the widely fluctuating seasonal swamp and drainage rivers ecotones are characterized by a less diverse and interdependent fish community. The degree of abiotic and biotic interdependence among fish in an ecotone is very important for the long term management of the Okavango Delta. Potential developers have to determine whether the effect of a given action by man is likely to result in a long term disturbance or merely in an elastic recoil to a more or less similar state. Recommendations are made on the conservation and management of Okavango fishes taking into account the ecological characteristics of the delta.
Keywords: Fishes -- Ecology -- Botswana; Fishes -- Botswana -- Okavango River Delta